2008
DOI: 10.1111/j.1741-3737.2008.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Processes Linking Social Class and Racial Socialization in African American Dual‐Earner Families

Abstract: We examined the links between social class, occupational self-direction, self-efficacy, and racial socialization in a sample of 128 two-parent African American couples raising adolescents. A series of multivariate, multilevel models revealed that mothers’ SES was connected to self-efficacy via its association with occupational self-direction; in turn, self-efficacy partially explained the association between occupational self-direction and racial socialization. The link between maternal self-efficacy and racia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Al though a few prior studies have examined these relationships (Hughes & Chen, 1997;Crouter et al, 2008), the current study is the first to our knowledge that (a) examined relationships between mothers' perceptions of racial/ethnic discrimination at work and adolescents' reports of racial/ethnic socialization in the home, and (b) explored differences in these associations across families from different racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 96%
“…Al though a few prior studies have examined these relationships (Hughes & Chen, 1997;Crouter et al, 2008), the current study is the first to our knowledge that (a) examined relationships between mothers' perceptions of racial/ethnic discrimination at work and adolescents' reports of racial/ethnic socialization in the home, and (b) explored differences in these associations across families from different racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, we expected that links between parents' and adolescents' religiosity would be stronger for adolescents who rated themselves higher on the exploration and commitment dimensions of ethnic identity. All analyses controlled for parental education, biological status of fathers, and adolescent age and birth order due to their potential roles in African American parent-adolescent relationships (Crouter, Baril, Davis, & McHale, 2008). …”
Section: Current Studymentioning
confidence: 99%
“…The few existing studies have provided some evidence of the association between African American fathers' racial identity beliefs and their socialization practices. Crouter et al () found that the centrality of race and personal beliefs regarding African Americans were associated with greater communication of cultural pride and preparation for bias messages among residential fathers. Using a profile‐oriented approach, White‐Johnson et al () found that parents who employed a multifaceted socialization strategy were likely to report that race was central to their self‐concept and more positive beliefs about their racial group than those who were low in racial socialization frequency.…”
Section: Traditional Approaches To Racial Socialization Processes Amomentioning
confidence: 99%